Alpha‐1‐antitrypsin deficiency‐related panniculitis: two cases with diverse clinical courses. (1st July 2017) - Storan, E. R.; O' Gorman, S. M.; Hawkins, P.; Aalto, L.; Murphy, A.; Markham, T.
Summary: Alpha‐1‐antitrypsin deficiency (AATD)‐related panniculitis is an extremely rare and underdiagnosed entity, and there is a paucity of data on its treatment. We report two cases of AATD‐related panniculitis. The first was a 24‐year‐old woman with known AATD who presented with painful leg ulcers refractory to treatment with corticosteroids and colchicine. She had a good response to α1‐antitrypsin infusions but required dose adjustment due to flares in disease activity. The second case was a 38‐year‐old woman who presented with painful nodules on the legs refractory to corticosteroid therapy. Laboratory investigations revealed severe AATD. She had an excellent response to colchicine therapy. In both these cases of AATD, panniculitis was the first clinical manifestation of the disease. AATD‐related panniculitis may have none of the typical clinical clues for AATD, such as a family history, cirrhosis or emphysema. Early identification may help prevent these complications from developing.